Leadership Training in the Nigerian Army: An Assessment of the Performance of Platoon Commanders - Ogbaji, Julia O.; Jeremiah, Jack (NIU Journal of Social Sciences, 2022)
The training of leaders in the military is of utmost importance especially that of the junior officer cadre. Junior officers in the Nigerian Army (NA) are expected to possess certain attributes; they must know what to do, when to do it and influence others to follow their lead. In other words, they should possess attributes that will make them effective leaders. This paper aims to examine the performance of Nigerian Army Commanders in the Junior Officer Cadre to establish the effectiveness of the training of junior officers and their performance as platoon commanders in the Nigerian Army. The findings of the study reveal that despite the update and construction of training curricula and training centres for Nigerian Army personnel, Junior officers’ performance on the field continues to fall short of expectations due to insufficient training, as he lacks the necessary tools to meet the tasks on the field. The demand for manpower is high, and the number of cadets undergoing training has grown over time with little correlation to the number of instructors. This has an impact on the quality of training thereby affecting their performance in the field. Through content analysis of secondary data, this work discusses the various challenges faced in the training of Junior Officer Commanders. The paper explains that there are diverse challenges in the leadership training of the Junior Officer Cadre which serve to hinder their effective performance as Platoon Commanders, and therefore the training currently adopted may not adequately address or prepare them for the tasks ahead. Thus, the paper concludes by recommending that Nigerian Army should consider collective training for its personnel in oversea military institutions; establish a combined training course for Platoon leaders and Platoon Sergeants in order to breach communication gap and create more synergy between them; expanding the roles of the Nigerian Army Cyberwarfare Command (NACWC) to train Junior officers in Information and Communications Technology (ICT) and its possible applications in warfare; construct training villages in order to portray realistic training environment to improve the performance of Junior officers in combat amongst others. Keywords: Military training, military leadership, Platoon Commanders, military education